PENGETAHUAN DAN SIKAP MASYARAKAT MENGENAI 4M PLUS DALAM PEMBERANTASAN SARANG NYAMUK DEMAM BERDARAH DENGUE DI PERUMAHAN KIJANG KENCANA III RT 02 RW 09 TAHUN 2022 - Pertiwi, Putri; Kholilah, Kholilah; Yusuf MF, M. (Jurnal Sanitasi Profesional Indonesia, 2022)
Indonesia is a country with the highest incidence of Dengue Hemorrhagic Fever (DHF) in Southeast Asia. The case of DHF is quite high where there are still several regencies/cities that have contributed to the increase in positive cases and deaths due to dengue, one of which is Tanjungpinang City. The number of dengue cases in the Tanjungpinang City on Janury - December 2021 had reached 323 cases. Therefore, it is necessary to give socialization to the community by carrying out 4M Plus in eradicating of dengue mosquito nests. The purpose of this study was to describe the knowledge and attitudes of the community regarding 4M Plus in eradicating mosquito nest of dengue hemorrhagic fever in Housing of Kijang Kencana III N/H 02/09 in 2022. This research used descriptive quantitative research method by questionnaire, with method purposive sampling and the number of sampels amounted 74 respondets. Results research showed that from all research respondents, there were 52 people (70.3 %) who had good knowledge about 4M Plus in eradicating dengue mosquito nest and 39 people (52.7%) had enough attitude about 4M Plus in eradicating dengue mosquito nest. Conclusion from study this that is majority type gender respondent is man as many as 60 people (81.1%), age respondent part big have range 46-65 years old as many as 42 people (56.8%), some big respondent with high school education 44 people (59.5%), respondents have good knowledge namely 52 people (70.3%) and respondent have enough attitude namely 39 people (52.7%). Suggestions that can be given for the community are to often carry out 4M plus activities in the eradicating mosquito dengue nest of hemorrhagic fever and always to keep the house clean.